The Relationship of Physical Activity and Nutritional Status to Physical Fitness of Students of SDN 2 Klepu, Sooko, Ponorogo Regency in the Covid-19 Pandemic - Fajar Furqon; Anung Priambodo; Advendi Kristiyandaru (BIRCU, 2021)
This study aims to examine the relationship between physical activity and nutritional status of SDN 2 Klepu students during the Covid-19 pandemic. Nutritional status and physical activity are both important factors in achieving optimal health, during a pandemic. This research uses multivariate correlational research. The purpose of correlational research is to determine the relationship between two or more variables, using purposive sampling technique, namely the technique of determining the sample with certain considerations, then the number of samples used is 36 students consisting of 14 students in class IV (four), 11 students in class V (five) and 11 students of class VI (six). As well as physical fitness tests using the Indonesian Physical Fitness Test (TKJI). The research instrument used in this study was the Physical Activity Questionnare Children (PAQ-C) questionnaire. The data analysis technique in this quantitative study uses quantitative descriptive methods aligned with research variables that focus on actual problems and phenomena that occur at the present time. Based on the results of the analysis of the price of rcount = -1.761 with r(table) = 0.3338 these results mean that there is a significant relationship between physical activity and the level of physical fitness of students, the analysis of the price of rcount = 1.948 with r(table) = 0.3338, can means that there is a significant relationship between nutritional status and the level of physical fitness of students, the results of multiple regression analysis were carried out by consulting the price of Fcount 3,568 > Ftable 3,27 at a significance level of 5% and Rcount = 0.401> Rtable = 0.3338, meaning the correlation coefficient it is significant. Ha which reads